Adaptable mobile user interface for securing e-learning environment - Aljbori, Mohanned Abdullah; Guirguis, Shawkat K; Madbouly, Magda M (Discoveries in Agriculture and Food Sciences, 2014)
E-Learning is a pedagogy empowered by Information and Communication technologies supporting education/training. While e-Learning exists over the past decade and a half, it is do not receiving considerable attention only in the recent times. Both Industry and Academia are heavily depending on e-Learning in streamlining their teaching process, and also E-learning has provided us with the capability of providing quality education to masses without restricting them to specific time or place, So that E-Learning become the most used and popular teaching method in universities with availability of E-learning tools and techniques, development of technology communications and networks. We can say that distance education’s popularity is increasing day by day and has become one of the most preferred methods for obtaining information. And it provides great facilities in many aspects according to traditional education. One of the most effective parameters in Electronic Learning or E-Learning systems’ success is the security of these systems. But this feature is ignored in the most of cases. An E-Learning system has different user groups such as authors, teachers and students. Each of these groups has special and unique security requirements. In this paper we will work on secure e-learning environment against unauthorized access through design a system for securing and control access to e-learning environment in distance learning institutions by adaptable mobile user interface associated with the token code generator Technology for learners who use mobile devices to access educational content.